2015
DOI: 10.1002/pat.3627
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of poly(4-vinylphenol) with embedded PbO nanoparticles

Abstract: An organic/inorganic nanocomposite film was synthesized using poly(4-vinylphenol) (PVPh) as an organic insulating polymer and PbO nanoparticles as a high-k inorganic material to serve as an organic insulator with enhanced dielectric properties. PbO nanoparticles were dispersed into propylene glycol monomethyl ether acetate, and a solution of PbO/PVPh nanocomposite was prepared by adding a crosslinker. The PbO nanoparticle content within the PVPh polymer matrix was varied, and the effects of this variation upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…The size and shape of these structures can be controlled using capping ligand as reported elsewhere [11,12]. It was reported that nanocomplexing with polymer can be used to combine the desirable properties of nanoparticles and polymer to be used in the Organic Thin Film Transistor (OTFT) [13]. In a similar way, the high surface area of semiconducting PbO nanostructures and electrical conductivity of polymers can be combined to be applied in the photovoltaic device.…”
Section: Introductionmentioning
confidence: 94%
“…The size and shape of these structures can be controlled using capping ligand as reported elsewhere [11,12]. It was reported that nanocomplexing with polymer can be used to combine the desirable properties of nanoparticles and polymer to be used in the Organic Thin Film Transistor (OTFT) [13]. In a similar way, the high surface area of semiconducting PbO nanostructures and electrical conductivity of polymers can be combined to be applied in the photovoltaic device.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, polymer-based materials have attracted attention for flexible electronic devices. Their flexibility, low cost, fast discharge rate, low dielectric loss, and simple manufacturing process make it possible to apply them to capacitors [5][6][7][8][9][10]. Among them, polyvinylidene fluoride (PVDF) shows a relatively high permittivity (k = 5-10), superhydrophobicity with low surface energy, remarkable mechanical strength, and chemical resistance.…”
Section: Introductionmentioning
confidence: 99%